Stable and switchable $$VO_2$$ -based metasurfaces in the near-infrared region - Elaheh Bazouband; Abdolnasser Zakery; Mahdieh Hashemi (Scientific Reports)
Abstract Metasurfaces, with their remarkable ability to control electromagnetic beams, provide great prospects for optical systems. Recently, active metasurfaces have gained more attention compared to passive ones due to their tunable functionality. However, most active metasurfaces just focus on tunability, this work presents $$VO_2$$ -based metasurfaces that consider both stable and tunable functions. The proposed design investigates the performance of metasurfaces at two distinct temperatures, $$T_1$$ = $$20^°$$ C and $$T_2$$ = $$80^°$$ C, for two input wavelengths $$λ _1$$ = 900 nm and $$λ _2$$ = 1500 nm. The metasurfaces include metalenses and gradient metasurfaces, each with a specific structure for different wavelengths, and are constructed with polarization-insensitive metaatoms. Numerical simulations reveal that at $$T_1$$ = $$20^°$$ C, the metasurfaces exhibit considerable focusing efficiencies and precise refracted beam directions for two input wavelengths. When the temperature changes to $$T_2$$ = $$80^°$$ C, the operations of metasurfaces remain stable for $$λ _1$$ = 900 nm due to the stable state of $$VO_2$$ at this wavelength range. In contrast, at $$λ _2$$ = 1500 nm, they undergo a sharp change because of an insulator-to-metal (IM) phase transition of $$VO_2$$ at this wavelength. Specifically, focusing efficiency drops to zero, and no refracted beam with a specified direction is observed at $$λ _2$$ = 1500 nm. Therefore, this work with the stable performance at $$λ _1$$ = 900 nm and the switchable performance at $$λ _2$$ = 1500 nm, would be applicable for thermally adaptive optical systems sensitive to temperature variation.